When Fear Surrounding Childbirth Leads Women to Request a Planned Cesarean Birth. (July 2022) - Bryanton, Janet; Beck, Cheryl Tatano; Morrison, Stephanie
Fear surrounding childbirth requires a more in-depth understanding from women's perspectives, especially those who request a planned cesarean due to that fear. Therefore, we explored primiparous and multiparous women's lived experiences of fear surrounding childbirth in relation to their decision to request a planned cesarean birth. We used Colaizzi's (1978) phenomenological method to interview 16 women from 4 provinces and to analyze the data. Women expressed numerous fears and most experienced more than one fear. Most feared their baby/babies being injured or dying during childbirth or developing complications themselves. Others feared experiencing a traumatic birth. Women described numerous emotional and physical manifestations of fear, and all believed that a planned cesarean birth would provide more control over the birth process. For some, the birth of their healthy baby/babies began a healing process, whereas others noted that their fear subsided or resolved upon confirmation that they would have a planned cesarean.